2014
DOI: 10.1155/2014/374079
|View full text |Cite
|
Sign up to set email alerts
|

Natural Product Polyamines That Inhibit Human Carbonic Anhydrases

Abstract: Natural product compound collections have proven an effective way to access chemical diversity and recent findings have identified phenolic, coumarin, and polyamine natural products as atypical chemotypes that inhibit carbonic anhydrases (CAs). CA enzymes are implicated as targets of variable drug therapeutic classes and the discovery of selective, drug-like CA inhibitors is essential. Just two natural product polyamines, spermine and spermidine, have until now been investigated as CA inhibitors. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…26,[39][40][41][42][43][44][45][46][47][48][49][50] Their biochemical features are known in detail for at least four classes, together with their distribution and role in various organisms. 32,33,41,[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] Inhibition and activation studies of many such enzymes from vertebrates, protozoa, fungi and bacteria have shown that they are drug targets for obtaining pharmacological agents of the diuretic, antiglaucoma, antiobesity, antiepileptic, anticancer or anti-infective type. [55][56][57][58]60 Many such enzymes also possess biotechnologic applications for biomimetic CO 2 capture processes.…”
Section: Introductionmentioning
confidence: 99%
“…26,[39][40][41][42][43][44][45][46][47][48][49][50] Their biochemical features are known in detail for at least four classes, together with their distribution and role in various organisms. 32,33,41,[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] Inhibition and activation studies of many such enzymes from vertebrates, protozoa, fungi and bacteria have shown that they are drug targets for obtaining pharmacological agents of the diuretic, antiglaucoma, antiobesity, antiepileptic, anticancer or anti-infective type. [55][56][57][58]60 Many such enzymes also possess biotechnologic applications for biomimetic CO 2 capture processes.…”
Section: Introductionmentioning
confidence: 99%
“…Herein we report on polyamines of natural origin, such as putrescine 1, spermidine 2 and spermine 3 ( Figure 1) as well as their structurally related derivatives of synthetic origin [10] or natural sources [11] which have, until now, been investigated as human (h) Carbonic Anhydrase (CA) inhibitors. Putrescine 1, spermidine 2 and spermine 3 represent the main pool of polyamines in the eukaryotic cells and are all derived from decarboxylation reactions of ornithine or S-adenosyl-methionine amino acids by the enzyme ornithine decarboxylase (ODC) [8].…”
Section: Polyamines In Biologymentioning
confidence: 99%
“…Another contribution in the field was from us in collaboration with the Davis Group at Eskitis on the series of spermidine secondary metabolites 27-31 ( Figure 6) [11]. Direct Structure-Activity-Relationship SAR between the CA inhibition and the chain length is also evident when comparing the kinetic data of the N-polysubstituted spermine derivatives 23-25 with the corresponding shorter analogues 19-22.…”
Section: Entrymentioning
confidence: 99%
See 2 more Smart Citations